Right Ventricular End-Diastolic Volume Combined With Peak Systolic Blood Pressure During Exercise Identifies Patients at Risk for Complications in Adults With a Systemic Right Ventricle - van der Bom, Teun; Winter, Michiel M.; Groenink, Maarten; Vliegen, Hubert W.; Pieper, Petronella G.; van Dijk, Arie P.J.; Sieswerda, Gertjan T.; Roos-Hesselink, Jolien W.; Zwinderman, Aeilko H.; Mulder, Barbara J.M.; Bouma, Berto J. (Journal of the American College of Cardiology, 2013)
The aim of this study was to identify which patients with a systemic right ventricle are at risk for clinical events. In patients with congenitally or atrially corrected transposition of the great arteries, worsening of the systemic right ventricle is accompanied by clinical events such as clinical heart failure or the occurrence of arrhythmia. At baseline, all subjects underwent electrocardiography, echocardiography, cardiopulmonary exercise testing, and cardiovascular magnetic resonance imaging. Clinical events comprised death, vascular events, tricuspid regurgitation requiring surgery, worsening heart failure, and (supra)ventricular arrhythmia. A Cox proportional hazards analysis was used to assess the most valuable determinants of clinical events. A total of 88 patients with a mean age of 33 years were included in the study. Sixty-five percent were men, and 28% had congenitally corrected transposition of the great arteries. During a follow-up period of 4.3 years, 31 patients (35%) experienced 46 clinical events for an annual risk of 12%. Right ventricular end-diastolic volume index measured by means of cardiovascular magnetic resonance imaging or multirow detector computed tomography (hazard ratio: 1.20; p < 0.01) and peak exercise systolic blood pressure (hazard ratio: 0.86; p = 0.02) were the strongest determinants of clinical events. Patients with a right ventricular end-diastolic volume index above 150 ml/m2 and peak exercise systolic blood pressure below 180 mm Hg were most likely to experience clinical events with an annual event rate of 19% versus 0.9% in patients without these risk factors. Patients with a right ventricular end-diastolic volume index above 150 ml/m2 and peak exercise systolic blood pressure below 180 mm Hg had a 20-fold higher annual event rate than patients without these risk factors. Regular cardiovascular magnetic resonance imaging and exercise testing are important in the risk assessment of these patients.